An efficient model for laminated composite thin-walled beams of open or closed cross-section and with or without in-filled materials. (15th January 2021) - Islam, Azizul; Sheikh, Abdul Hamid; Bennett, Terry; Thomsen, Ole Thybo
Abstract: The paper presents a new modeling technique for accurately predicting the complex behavior of thin-walled open and closed section beams made of fiber-reinforced laminated composite materials. The new modeling technique is significantly computational-efficient compared to detailed finite element modeling. In this technique, the complete 3D stress analysis problem consisting of all effects and their couplings is systematically decomposed into a 2D problem applicable to the beam section, and a 1D problem applicable along the beam length. The capability of the technique is not only suitable for thin-walled beams but also applicable for modeling beams with solid, thick-walled sections as well as thin/thick-walled composite beams with in-filled materials. To analyze beams with any arbitrary cross-sectional geometry, a 2D finite element (FE) model is used for solving the 2D sectional problem, while the 1D problem for the global load response of the beams is solved by a 1D FE model utilizing the sectional stiffness parameters obtained from the 2D model. The proposed technique is validated using experimental and numerical results, which show the excellent performance of the model. New results for a range of beam sections are developed using the presented method and validated against detailed FE modeling.